2001
DOI: 10.3354/meps218267
|View full text |Cite
|
Sign up to set email alerts
|

Response of naïve two-spotted gobies Gobiusculus flavescens to visual and chemical stimuli of their natural predator, cod Gadus morhua

Abstract: In order to determine whether the anti-predator response of gobies to cod Gadus morhua is inherited, naïve two-spotted gobies Gobiusculus flavescens were exposed to visual or chemical cod stimuli, in order to determine whether such stimuli would trigger an innate anti-predator response. Groups of 10 naïve adult two-spotted gobies were tested for their distribution between 2 habitats in an aquarium: 1 'safe' and 1 'risky' habitat, in which a cod was presented either visually or by its odour. Equal amounts of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 34 publications
3
29
0
Order By: Relevance
“…Second, It has been argued that prey animals' responses to the presence of predators is under strong selection to be a highly generalized and stereotypical response – though in some cases requiring experiential learning to become stereotypical. This argument is supported by the common usage of single individuals as predator stimuli in previous studies of predator avoidance behavior in fishes [7], [9], [24]. For these reasons, we did not find it necessary to conduct replicated trials using multiple cichlids as predator stimuli.…”
Section: Methodsmentioning
confidence: 52%
See 3 more Smart Citations
“…Second, It has been argued that prey animals' responses to the presence of predators is under strong selection to be a highly generalized and stereotypical response – though in some cases requiring experiential learning to become stereotypical. This argument is supported by the common usage of single individuals as predator stimuli in previous studies of predator avoidance behavior in fishes [7], [9], [24]. For these reasons, we did not find it necessary to conduct replicated trials using multiple cichlids as predator stimuli.…”
Section: Methodsmentioning
confidence: 52%
“…This hypothesis has received much support among studies of adult fish [7], [8], [21; reviewed in refs. 22], [23], and in a handful of studies investigating the use of predator chemical cues by juvenile fish.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Utne-Palm (2001) found that naïve two-spotted gobies (Gobiusculus flavescens, Gobiidae) subsequently avoided the habitat where they last saw a live cod predator (Gadus morhua, Gadidae), but avoided cod odour only after observing cod on three successive occasions. Brown ) similarly found that rainbowfish (Melanotaenia spp., Melanotaeniidae) avoided habitats where they had previously encountered a model of their natural predator, the mouth almighty (Glossamia aprion, Apogonidae).…”
Section: Avoiding Dangerous Habitatsmentioning
confidence: 99%